(untitled) (مجلة البيان العلمية, 2023)
Lung cancer, also known as bronchial cancer about 98-99% of all lung cancers is precancerous, is a malignant lung tumour characterized by uncontrolled cell growth in lung tissue, and consists of two main types, small cell lung cancer (SCLC) and Non small cell lung cancer , Non Small (NSCLC) .The most common symptoms are coughing (including coughing up blood), weight loss ,shortness of breath, and chest pain. The vast majority (85%)of lung cancer cases are caused by long-term tobacco smoking. Lung cancer can be seen on chest radiographs and computerized tomography (CT) scans. The diagnosis is confirmed by biopsy ,which is usually performed by Bronchoscopy or computed tomography guidance. Medications used in the treatment of lung cancer in the Department of Oncology, Tobruk ,and their prevalence rate in the city were limited. 48 lung cancer patients were registered in the city’s oncology department, including 6 women and 42 men, and statistics were collected from 2018 to 2020. Among the 48 lung cancer patients,19 of them were from outside Tobruk and 29 from Tobruk, and their age groups ranged between 40 and 85 years ,and we find that the largest number of patients are those over 60 years old ,and this agrees with several studies precedent. The drugs used for treatment were: CISPLATIN (9%), PEMETREXED (12%) , TAXOTARE (3%) , KEYTRUDA (4%) , AVASTIN (9%) , GEMZAR (14%) , PACLITAXEL (13%)